A Novel Modified Tornado Optimizer with Coriolis Force Based on Levy Flight to Optimize Proportional Integral Derivative Parameters of DC Motor - Diego Oliva; Farhad Soleimanian Gharehchopogh; Vugar Hacimahmud Abdullayev; Widi aribowo; Asmunin Asmunin; Andi Iwan Nurhidayat (Universitas Negeri Surabaya or The State University of Surabaya, 2025)
One kind of electric motor that runs on direct current (DC) is called a DC (Direct Current) motor. This motor uses the interaction of electric current and magnetic fields to transform electrical energy into mechanical energy, or motion. Applications requiring exact speed and torque control frequently use DC motors. By minimizing errors (differences between setpoints and actual values), proportional-integral-derivative (PID) control is a control technique used to govern dynamic systems to reach desired conditions (setpoints). PID creates an ideal control signal by combining three elements. The Modified Tornado optimizer-based Coriolis force (TOC) method for DC motor control is presented in this article. The paradigm for the TOC approach is the Tornado Optimizer-Based Coriolis Force Algorithm, a metaheuristic that leverages tornado dynamics and the effect of the Coriolis force to address difficult optimization problems. According to this study, the TOC method can be improved by implementing the Levy Flight methodology. According to the results of tests employing optimal functions, the LTOC technique may broaden exploration and exploitation. Meanwhile, when the LTOC technique is applied as a DC motor controller, the optimal overshoot response value is achieved. The LTOC approach outperforms the TOC method by 0.014% and 0.037%, respectively, in terms of ITSE and ITAE values.